Understanding and Minimizing VOC Losses in All‐Perovskite Tandem Photovoltaics. Issue 3 (2nd December 2022) - Thiesbrummel, Jarla; Peña‐Camargo, Francisco; Brinkmann, Kai Oliver; Gutierrez‐Partida, Emilio; Yang, Fengjiu; Warby, Jonathan; Albrecht, Steve; Neher, Dieter; Riedl, Thomas; Snaith, Henry J.; Stolterfoht, Martin; Lang, Felix
Abstract: Understanding performance losses in all‐perovskite tandem photovoltaics is crucial to accelerate advancements toward commercialization, especially since these tandem devices generally underperform in comparison to what is expected from isolated layers and single junction devices. Here, the individual sub‐cells in all‐perovskite tandem stacks are selectively characterized to disentangle the various losses. It is found that non‐radiative losses in the high‐gap subcell dominate the overall recombination in the baseline system, as well as in the majority of literature reports. Through a multi‐faceted approach, the open‐circuit voltage ( V OC ) of the high‐gap perovskite subcell is enhanced by 120 mV. Employing a novel (quasi) lossless indium oxide interconnect, this enables all‐perovskite tandem solar cells with 2.00 V V OC and 23.7% stabilized efficiency. Reducing transport losses as well as imperfect energy‐alignments boosts efficiencies to 25.2% and 27.0% as identified via subcell selective electro‐ and photo‐luminescence. Finally, it is shown how, having improved the V OC, improving the current density of the low‐gap absorber pushes efficiencies even further, reaching 25.9% efficiency stabilized, with an ultimate potential of 30.0% considering the bulk quality of both absorbers measured using photo‐luminescence. These insights not only show an optimization example but also a generalizable evidence‐based optimization strategy utilizing optoelectronic sub‐cell characterization. Abstract : Understanding and minimizing performance losses in all‐perovskite tandem solar cells is crucial to accelerate advancements toward commercialization, yet challenging, since the individual subcells cannot be assessed directly in a monolithic interconnection. Thorough subcell‐selective characterizations provide crucial feedback to improve monolithic all‐perovskite tandem solar cells with optimized subcells and a lossless interconnect toward their true material potential.